PENGARUH KONSENTRASI NUTRISI HIDROPONIK SISTEM NFT PADA PERTUMBUHAN DAN HASIL TANAMAN SAWI (Brassica juncea L.) - Nur Widyaningsih; Ardaniah Ardaniah; Primadiyanti Arsela (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2026)
This study sought to assess the impact of different hydroponic nutrient concentrations on the development and production of mustard greens (Brassica juncea L.) farmed via the Nutrient Film Technique (NFT) system, and to identify the best concentration level. The experiment was executed in a greenhouse situated in Seniung Jaya Village, Pasir Belengkong District, Paser Regency, throughout November to December 2025. A Completely Randomized Design (CRD) with one factor was utilized, including four nutrient concentration treatments, each duplicated three times. The measured characteristics were plant height, leaf count, and fresh weight. Data were evaluated utilizing analysis of variance (ANOVA), succeeded by a Least Significant Difference (LSD) test at the 5% significance level upon detection of significant differences. The findings demonstrated that nutrition content significantly influenced all measured parameters. Six weeks post-transplantation, the treatment with the lowest concentration yielded the greatest measurements for plant height, leaf count, and fresh weight. Conversely, elevated nutrient concentrations often decreased plant growth and production. The data indicate that an ideal nutrient level exists for enhancing plant performance, whereas high nutrient concentrations may adversely impact growth. Nutrient balance is more crucial than excessive nutrient input in hydroponic growth systems.